Utilization of gastroprotective strategies for nonsteroidal anti-inflammatory drug-induced gastrointestinal events in a major teaching hospital - Lee HL; Chua SS; Mahadeva S (Dove Medical Press, 2016)
Hooi Leng Lee,1 Siew Siang Chua,1 Sanjiv Mahadeva2 1Department of Pharmacy, 2Department of Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia Background and purpose: Clinical guidelines recommend the prescribing of gastroprotective strategies in nonsteroidal anti-inflammatory drug (NSAID) users with risk factors for gastrointestinal (GI) ulcer or ulcer complications. However, these guidelines are not often translated into clinical practice. Therefore, the aim of this study was to investigate the utilization of gastroprotective strategies for NSAID-induced upper GI events in at-risk users in a major teaching hospital. Patients and methods: A cross-sectional, observational, pharmacy-based study was conducted in a major Asian institution with both primary and secondary health care services. This study involved the screening of prescriptions for regular NSAIDs, and patients who met the inclusion criteria were recruited and interviewed using a questionnaire. Results: Of the 409 participants recruited, 83.1% had at least one GI risk factor, of whom 70.3% did not receive appropriate gastroprotection. The most common GI risk factor was the use of high-dose NSAIDs (69.2%), followed by participants aged 65 years and older (22%) and concomitant use of low-dose aspirin (11.7%). Appropriate gastroprotective strategies utilized consisted of the use of a cyclooxygenase (COX)-2 inhibitor alone or a nonselective NSAID plus a proton pump inhibitor (PPI) in the moderate-risk group and a COX-2 inhibitor plus a PPI in the high-risk group. Gastroprotective strategies were underutilized in 67.1% of at-risk participants and overutilized in 59.4% of those without risk factors. Co-prescription of a histamine-2 receptor antagonist at lower-than-recommended doses constituted 59% of the inappropriate gastroprotective agents used. Logistic regression analysis revealed patients aged 65 years and older (odds ratio, 1.89; 95% CI =1.15–3.09) as a predictor for the prescribing of gastroprotection by the clinicians. Conclusion: Approximately 70% of at-risk NSAID users, mainly on high-dose NSAIDs, were not prescribed appropriate gastroprotective strategies. Further measures are warranted to improve the safe prescribing of regular NSAIDs. Keywords: NSAID, COX-2 inhibitor, risk factor, proton pump inhibitor